The Diversion For Children In Front Of The Law In Traffic Accident Cases - Bagus Jatmiko; Bambang Tri Bawono (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to identify and analyze the implementation of diversion in the settlement of traffic accident cases committed by children in the context of legal certainty; knowing and analyzing the obstacles and solutions to the application of diversion in the settlement of traffic accident cases committed by children in the context of law enforcement that leads to restorative justice. This research approach method uses a sociological juridical approach. The conclusion of this study is that law enforcement officers in carrying out their duties of investigating, prosecuting, examining and determining case decisions for children who are in conflict with the law in traffic accident cases should prioritize the application of diversion as an alternative to the application of imprisonment. Massive socialization of diversion is needed to the community. The government should provide diversion facilities and infrastructure in order to guarantee protection for children.